Live birth rate after female fertility preservation for cancer or haematopoietic stem cell transplantation: a systematic review and meta-analysis of the three main techniques; embryo, oocyte and ovarian tissue cryopreservation. Issue 3 (24th November 2022) - Fraison, E; Huberlant, S; Labrune, E; Cavalieri, M; Montagut, M; Brugnon, F; Courbiere, B
Abstract: STUDY QUESTION: What are the chances of achieving a live birth after embryo, oocyte and ovarian tissue cryopreservation (OTC) in female cancer survivors? SUMMARY ANSWER: The live birth rates (LBRs) following embryo and oocyte cryopreservation are 41% and 32%, respectively, while for IVF and spontaneous LBR after tissue cryopreservation and transplantation, these rates are 21% and 33%, respectively. WHAT IS KNOWN ALREADY: Currently, fertility preservation (FP) has become a major public health issue as diagnostic and therapeutic progress has made it possible to achieve an 80% survival rate in children, adolescents and young adults with cancer. In the latest ESHRE guidelines, only oocyte and embryo cryopreservation are considered as established options for FP. OTC is still considered to be an innovative method, while it is an acceptable FP technique in the American Society for Reproductive Medicine guidelines. However, given the lack of studies on long-term outcomes after FP, it is still unclear which technique offers the best chance to achieve a live birth. STUDY DESIGN, SIZE, DURATION: We performed a systematic review and meta-analysis of published controlled studies. Searches were conducted from January 2004 to May 2021 in Medline, Embase and the Cochrane Library using the following search terms: cancer, stem cell transplantation, FP, embryo cryopreservation, oocyte vitrification, OTC and reproductive outcome. PARTICIPANTS/MATERIALS, SETTING, METHODS: A total of 126 full-text articles were preselected from 1436 references based on the title and abstract and assessed via the Newcastle–Ottawa Quality Assessment Scale. The studies were selected, and their data were extracted by two independent reviewers according to the Cochrane methods. A fixed-effect meta-analysis was performed for outcomes with high heterogeneity. MAIN RESULTS AND THE ROLE OF CHANCE: Data from 34 studies were used for this meta-analysis. Regarding cryopreserved embryos, the LBR after IVF was 41% (95% CI: 34–48, I 2 : 0%, fixed effect). Concerning vitrified oocytes, the LBR was 32% (95% CI: 26–39, I 2 : 0%, fixed effect). Finally, the LBR after IVF and the spontaneous LBR after ovarian tissue transplantation were 21% (95% CI: 15–26, I 2 : 0%, fixed-effect) and 33% (95% CI: 25–42, I 2 : 46.1%, random-effect), respectively. For all outcomes, in the sensitivity analyses, the maximum variation in the estimated percentage was 1%. LIMITATIONS, REASONS FOR CAUTION: The heterogeneity of the literature prevents us from comparing these three techniques. This meta-analysis provides limited data which may help clinicians when counselling patients. WIDER IMPLICATIONS OF THE FINDINGS: This study highlights the need for long-term follow-up registries to assess return rates, as well as spontaneous pregnancy rates and birth rates after FP. STUDY FUNDING/COMPETING INTEREST(S): This work was sponsored by an unrestricted grant from GEDEON RICHTER France. The authors have no competing interests to declare. REGISTRATION NUMBER: CRD42021264042.